Genetic steroid disorders - New, Maria I., 1928- (Academic Press, 2014)
This is a comprehensive book addressing steroid disorders from hormonal, genetic, psychological, and surgical perspectives. It is meant to educate adult and pediatric endocrinologists, clinical geneticists, genetic counselors, reproductive endocrinologists, neonatologists, urologists, and psychoendocrinologists. It will assist these specialists in the diagnosis and treatment of steroid disorders. The book is written for postgraduate and faculty-level physicians. The content consists of steroid disorders, genetic bases for the disorder and case presentations of each disorder. Provides a common language for professionals to discuss and diagnose genetic steroid disorders. Includes the very latest details on genetic tests and diagnoses. Offers a strong understanding of the molecular basis for the diseases and therefore correct diagnosis and treatment of steroid disorders. Presents insight into which medications to use based on the genetic makeup of a patient. Teaches the best strategies and most effective use of genetic information in the patient counseling setting.